1983
DOI: 10.1111/j.0022-3646.1983.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF SELECTED HERBICIDES ON ZYGOSPORE GERMINATION AND GROWTH OF CHLAMYDOMONAS MOEWUSII (CHLOROPHYCEAE, VOLVOCALES)11

Abstract: A laboratory study was conducted, to examine and compare the sensitivity of vegetative cells and zygospores of Chlamydomonas moewusii Gerloff to 20 different herbicides. Under the culture conditions employed, both vegetative growth and zygospore germination were affected by certain herbicides and not by others. Over a concentration range from 1.0–80.0 μM, growth was inhibited to various degrees by herbicides containing ametryne, paraquat, endothall, diquat, diuron, linuron, propanil, dinoseb, ioxynil, atrzine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In addition to the studies on vegetative cells of Anabaena doliolurn, Kashyap and Pandey (1982) also examined the response of spores of this cyanobacterium to butachlor; the spores were found to be approximately four times more resistant than vegetative cells. Very few workers have considered the possibility of tolerance differences between vegetative cells and resting stages (Cain and Cain 1983). In a later study, Anabaena doliolurn was found to be more tolerant than either Nostoc rnuscorurn or Anacystis nidulans to butachlor, lethal concentrations being 20, 5, and 2.5 ppm, respectively (Pandey and Kashyap 1986).…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…In addition to the studies on vegetative cells of Anabaena doliolurn, Kashyap and Pandey (1982) also examined the response of spores of this cyanobacterium to butachlor; the spores were found to be approximately four times more resistant than vegetative cells. Very few workers have considered the possibility of tolerance differences between vegetative cells and resting stages (Cain and Cain 1983). In a later study, Anabaena doliolurn was found to be more tolerant than either Nostoc rnuscorurn or Anacystis nidulans to butachlor, lethal concentrations being 20, 5, and 2.5 ppm, respectively (Pandey and Kashyap 1986).…”
mentioning
confidence: 94%
“…Others (ametryne, dinoseb, diquat, endothall, ioxynil, linuron, paraquat, and propanil) inhibited to some extent both vegetative growth and zygospore germination. Diuron, atrazine, alachlor, and prometon inhibited only vegetative growth, whereas fenac and picloram inhibited only zygospore germination (Cain and Cain 1983). The authors concluded that zygospores may be more resistant than vegetative cells to some but not all herbicides.…”
mentioning
confidence: 97%
See 3 more Smart Citations